Síntesis de catalizadores para producción de hidrógeno mediante reformado con vapor de compuestos oxigenados - González-Gil, Rafael (UMA Editorial, 2025)
This thesis addresses the sustainable production of hydrogen through steam reforming of oxygenated compounds, which are key components of bio-oil—a liquid derived from the fast pyrolysis of biomass. As the conventional method of hydrogen production via natural gas reforming is unsustainable, the valorization of these compounds is proposed, considering their potential as hydrogen carriers or alternative fuels. The selected model compounds were acetone, ethanol, and the DME/methanol pair. Active catalysts were developed based on the monometallic Ni/Al₂O₃ system, commonly used in industry, and were modified by incorporating noble (Rh) and transition metals (V) to improve performance depending on the oxygenated compound being reformed. These bimetallic catalysts were thoroughly characterized, and their activity, selectivity, and stability were evaluated. Additionally, the interaction between Ni and the second metal was studied to understand the reaction mechanisms and surface behavior. The addition of Rh enhanced catalytic activity, improved Ni dispersion, and reduced carbon deposition, especially in acetone and ethanol reforming, with ethanol showing higher hydrogen selectivity. A structured multimetallic catalyst (RhCeNi) was designed and tested at pilot scale for ethanol reforming, achieving 98% conversion at 923 K and producing a hydrogen-rich stream suitable for PEM fuel cells. Regarding DME, its easy storage and transport, along with compatibility with existing LPG infrastructure, make it a promising hydrogen source and alternative fuel. The steam reforming of DME proceeds via hydrolysis followed by methanol reforming, facilitated by strong Lewis acid sites on the catalyst surface.

Overall, this thesis contributes to the understanding and development of efficient catalytic systems for hydrogen production from biomass-derived compounds. It supports the use of these molecules as hydrogen carriers and promotes the transition to decarbonized energy and transport systems with hydrogen as a key energy vector.
Keywords: Materiales nanoestructurados - Tesis doctorales; Catálisis; Hidrógeno; Procesos; Compuestos oxigenados